Association Between Systemic Immune-Inflammation Index and Symptomatic Intracranial Hemorrhage in Acute Ischemic Stroke Patients Undergoing Endovascular Treatment - Yang, Yuan; Cui, Ting; Bai, Xueling; Wang, Anmo; Zhang, Xuening; Wan, Jincheng; Wang, Changyi; Lu, Kun; Hu, Fayun; Wu, Bo (Current Neurovascular Research, 2022)
Background/Objective: Systemic immune-inflammation index (SII) is a novel inflammatory factor, which may be involved in the destruction of the blood-brain barrier (BBB) after acute ischemic stroke (AIS); however, the association between SII and symptomatic intracranial hemorrhage (sICH) in AIS patients undergoing endovascular treatment (EVT) remains unclear. Methods: Patients with acute ischemic stroke due to large vessel occlusion (AIS-LVO) who underwent EVT were consecutively enrolled. Blood samples were collected in the emergency room and SII was calculated by neutrophils × platelets/lymphocytes. Participants were categorized into tertiles according to admission SII. The main outcome was defined as the occurrence of sICH, following the European Cooperative Acute Stroke Study III (ECASS-III) criteria. Results: A total of 379 AIS-LVO patients with EVT were enrolled (median age = 71 years, 52.5% males). The median baseline National Institutes of Health Stroke Scale (NIHSS) score was 15 (IQR, 12-18). The median of SII was 820.9 × 109/L (IQR, 473.1-1345.2). Forty-three (11.3%) patients developed sICH. SII was found to be independently associated with sICH after EVT (adjusted odd ratio (OR) = 1.005 (per 10 units increase); 95% confidence interval (CI): 1.002-1.008; p = 0.002). Compared to patients in the lowest SII tertile, patients in the highest tertile had a higher risk of sICH (adj-OR 3.379; 95% CI 1.302-8.768; p = 0.012). The risk of sICH increased with the increase of SII in a dose-dependent manner (p for trend = 0.004). There was no interaction between potential modifiers and SII on sICH. Conclusion: Admission SII is positively associated with sICH in AIS-LVO patients treated with EVT. These results need to be confirmed in future studies.
Keywords: complication